A new supramolecular binder strongly enhancing the electrochemistry performance for lithium–sulfur batteries. Issue 92 (4th November 2019) - Zuo, Yuan; Liu, Ruliang; Zhang, Xingcai; Nadimicherla, Reddeppa; Huang, Junlong; Lu, Yuheng; Liu, Shaohong; Wu, Dingcai; Fu, Ruowen
Abstract : We report for the first time a novel supramolecular eutectic liquid (SEL) binder consisting of diphenylamine and benzophenone, which exhibits excellent performance for Li–S batteries. Abstract : As one of the indispensable components in lithium–sulfur batteries, the binders greatly impact battery performance. Herein, we report a new multifunctional supramolecular eutectic liquid (SEL) binder, consisting of diphenylamine (DP) and benzophenone (BP), which enables a strongly improved conductive network and anchored polysulfides for high-performance lithium–sulfur batteries. Compared with the traditional polyvinylidene fluoride (PVDF) binder, the SEL binder demonstrates remarkable improvement in both the mechanical performance and the capacity retention (83% over 200 cycles at 1C).